2014
DOI: 10.1007/s40291-013-0070-3
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Profiling of EGFR/HER Receptors for Personalized Treatment of Gynecologic Cancers

Abstract: The primary gynecologic cancers include cancers of the endometrium, ovary, and cervix. Worldwide, cervical cancer is the most common gynecologic cancer, whereas endometrial cancer is the most common in the US. Ovarian cancer is the fifth most deadly cancer in women, with 5-year survival rates for advanced disease at only 27%. As such, there is an urgent need for reliable screening tools and novel targeted therapeutic regimens for these malignancies. The EGFR/HER family of receptors has been associated with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 104 publications
2
36
0
1
Order By: Relevance
“…Wright et al found that the expression of α 1 and α 6 -adhesion molecules which are essential for invasion or interaction with the extracellular matrix were decreased in the extravillous trophoblastic cell line by blocking epidermal growth factor receptor (EGFR/HER1) activation (21). In contrast, EGFR is overexpressed in approximately 50% of endometrial tumors and is significantly associated with decreased survival in patients with Type II endometrial cancer (22,23).…”
Section: Discussionmentioning
confidence: 99%
“…Wright et al found that the expression of α 1 and α 6 -adhesion molecules which are essential for invasion or interaction with the extracellular matrix were decreased in the extravillous trophoblastic cell line by blocking epidermal growth factor receptor (EGFR/HER1) activation (21). In contrast, EGFR is overexpressed in approximately 50% of endometrial tumors and is significantly associated with decreased survival in patients with Type II endometrial cancer (22,23).…”
Section: Discussionmentioning
confidence: 99%
“…Epidermal growth factor receptor (EGFR) has been extensively studied in OC, but its prognostic role and its relevance as therapeutic target remain controversial [32].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Endometrial cancer: Samples taken from 28 woman with endometrial cancer showed three different mutations in separate patients. L688F and E690K were in exon 18 and K754E in exon 19, which is in contrast to others responsive to lapatinib treatment (Leslie et al, 2013;Reyes et al, 2014) Colorectal cancer: EGFR mutation status of 13 patients among 35 male and 23 female patients at different stages of colorectal cancer showed exon 20 mutation but not exons 18,19 and 21 mutations (Oh et al, 2011). S492R EGFR ectodomain mutation also increases the mutation rate and mABCH12 was suggested to prevent the effect of mutated EGFR (Dong et al, 2019).…”
Section: Homologymentioning
confidence: 62%